Catolicismo e Natureza: a emergência do cuidado com a casa comum - Portes, Ana Lucia Araújo (Sacrilegens, 2020)
Catholicism and nature: the emergence of caring for the common home Ecological and care for nature issues have been the focus of discussions by various sectors today. Laudato Si, an encyclical promulgated by Pope Francis in 2015, has a broad and emergency character, addressed to all those who feel committed and co-responsible for the care of creation, with the objective especially "to enter into dialogue with all about our common home "(LS 3) Therefore, this study aims to address the issues raised today about caring for nature from the perspective of Catholicism, emphasizing why it is so urgent to discuss this topic at this historic moment. Abstract : Catholicism, Nature, Environment, Sustainability, Laudato Si.